Health Consequences of Medoroga (Obesity) and its Management Through Ayurveda and Yoga - Patnaik, Supriti (International Research Journal of Ayurveda & Yoga, 2022)
Weight gain is a natural physiological process, but sometimes it increases to the point of development where it may impair health and invites a number of disorders with high morbidity and mortality. Meda which is the fourth one of the seven components of the body known as Saptadhatu is the contemporary term used against fat and the disease caused by this is Medoroga or Obesity. In Charaka Samhita it is described as one among Astaninditiya (Contemptible)Purusa. It is said that it is comparatively easy to help an underweight person, rather than an overweight person. The advancement of industrialization and communication is contributing towards sedentary life styles, in turn causes non-communicable diseases like obesity. It has always created problem owing to the state of helplessness due to limitation for enjoying an active life. It is associated with many serious and life threatening complications, such as Hypertension, Diabetes mellitus, Atherosclerosis, Ischemic heart disease, Cardio-vascular accidents, Myocardial infarction, etc. Obesity being the risk factor for these diseases and hence prevention of obesity will decrease the chances of such diseases. Through Ayurveda and Yoga practice we can achieve the healthy life.